The Effect of Dental Health Programs in Pre-pregnancy into Low Birth Weight at Brati Public Health Center - Nira Ardlina; Rahmadika Kemala Firdausia (Odonto : Dental Journal, 2023)
Background: The pregnancy period is prone to various dental health conditions that can affect pregnant women’s health and cause growth and development problems for the fetus. Neglecting dental health during pregnancy causes complications at birth, including low birth weight. This study aims to determine the effect of dental health programs for pre-pregnancy women into low birth weight at Brati Public Health Center. Method: This research used secondary data from 80 women who participated in dental health programs for pre-pregnancy women and Antenatal Care (ANC) participants at Brati Health Center who were monitored until birth between January 2020 – June 2023. The data obtained was assessed in a questionnaire regarding the completeness of the dental health programs for pre-pregnancy women, consisting of education, examination, and dental care carried out before and after pregnancy. The data analysis used was the Mann Whitney test. Result: Pre-pregnancy women who completed the dental health programs had a higher average birth weight (3.095 kg) than those who did not complete the program (2.076 kg). Mann Whitney test result revealed an effect between the completeness of dental health programs on pre-pregnancy to birth weight (p=0.000). Conclusion The dental health programs for pre-pregnancy women affect the birth weight. Dental health programs for pre-pregnancy women should be carried out before pregnancy occurs, starting from the examination and education of the prospective bride. Collaboration between antenatal and dental health service providers is needed to increase access to dental prevention and treatment services needed by pre-pregnancy dan pregnant women.